From Arabization to EMI: Tracing the Evolution of English in Algerian Education - CHETTIBI, Rim Racha (Journal of Human Sciences, 2025)
This article provides a historical overview of educational reforms in Algeria with a particular focus on the development of English language education. From post-independence Arabization efforts to the recent introduction of English in primary schools, Alge-ria’s language-in-education policy has undergone significant transformations influenced by political, social, and global factors. While French has long dominated the educational and administrative landscape, recent reforms reflect a growing recognition of English as a global lingua franca. This paper explores key reforms that have shaped the status of English in Algerian edu-cation, analyzes the motivations behind policy shifts, and discusses the challenges and implications of integrating English more systematically into the curriculum.